Quality of Care during Neonatal Resuscitation in Kakamega County General Hospital, Kenya: A Direct Observation Study. (29th October 2017) - Shikuku, Duncan N.; Milimo, Benson; Ayebare, Elizabeth; Gisore, Peter; Nalwadda, Gorrette
Abstract : Background . Birth asphyxia is the leading cause of neonatal mortality in Kenya. Quality care during neonatal resuscitation (NR) can contribute to a reduction in neonatal mortality related to birth asphyxia by 30 percent. This study assessed the quality of care (QoC) during NR for newborns with birth asphyxia. Methods . Direct observations of 138 newborn resuscitations were done in labor ward and maternity theatre. Twenty-eight healthcare providers were observed 3–5 times using a structured checklist. Descriptive and inferential statistics were calculated and quality of care scores computed. Ordered logistic regression model identified HCPs characteristics associated with the QoC scores during NR. Results . Overall QoC scores were good for airway clearance (83%). Suctioning in meconium presence (40%) was poorly performed. Years of experience working in maternity were associated with good drying/stimulation ( β = 1.86, P = 0.003, CI = 0.626–3.093) and airway maintenance ( β = 1.887, P = 0.009, CI = 0.469–3.305); nurses were poor compared to doctors during initial bag and mask ventilation ( β = −2.338, P = 0.05, CI = −4.732–0.056). Conclusion . Key steps in NR are poorly performed during drying and warmth, airway maintenance in meconium presence, and ventilation. Mentorship with periodic refresher training can improve the care provided during NR.